Immobilized Β-Galactosidase-Mediated Conversion Of Lactose Process, Kinetics And Modelling Studies - Gonawan, Fadzil Noor (2017)
Lactose can be converted to valuable product of galacto-oligosaccharides (GOS) through β-galactosidase (β-Gal)-catalyzed reaction via hydrolysis and transgalactosylation. A high yield of GOS is obtained when the reaction process is carried out in enzymatic membrane reactor (EMR) of which the mechanism remain poorly understood. The mass transfer behaviour of substrate or solute to the biocatalytic and through the membrane layers are expected to influence the course of the reaction as well as the biocatalytic performance in the EMR. The aim of this study was to analyze the effect of mass transfer profile in the enzymatic hollow fiber membrane reactor (HFMR) on the immobilized β-Gal-mediated conversion of lactose. Investigation of the reaction process indicated that the formation of GOS was highly influenced by initial lactose concentration and β-Gal activity. Galactose has been found to be competitive inhibitor and able to decrease the formation of GOS. The HFMR with immobilized β-Gal was developed to continuously remove the inhibitor (galactose) and improved the reaction performance. Hydrodynamic study of shear rate on the membrane surface has suggested that the HFMR is best operated with an ultrafiltration from the lumen to shell side. This configuration gives homogeneous distribution of shear rate which is important for the immobilization of β-gal on the membrane surface. The β-Gal was immobilized on the polyethyleneimine (PEI)-layered surface of the membrane via simultaneous adsorption and fixation with glutaraldehyde (GA). The activity yield was influenced by the concentration of PEI, GA and β-Gal. In general, the specific productivity of the GOS was increased in the HFMR compared to the classical batch system. The reaction performance in the HFMR was greatly influenced by the trans-membrane pressure (TMP) compared to the nominal feed flow rate. The formation of GOS was highest at TMP of 0.5 bar. In order to understand this behaviour, kinetic of reaction and mass transfer studies were carried out. The kinetic model incorporated with the effect of lactose, glucose, galactose, trisaccharides and tetrasaccharides concentrations was successfully developed and validated. Meanwhile, an appropriate mass transfer model incorporated with the effect of membrane characteristics, concentration of solutes in bulk solution and the formation of cake layer were employed. The simulation study indicated that, the reaction rate for the formation of GOS was highly influenced with the operating TMP. The maximum formation of GOS was obtained at TMP of 0.5 bar which is in agreement with the result obtained from the experiment. The formation of cake-layer at higher TMP (>0.5 bar) reduced the mass transfer of solutes through the biocatalytic membrane. Therefore, the reaction rates were decreased as the TMP was further increased to 0.8 bar although the separation of the galactose inhibitors was improved. Hence, it was concluded that the mass transfer of solutes to the biocatalytic membrane was the determining factor to obtain high yield of GOS via immobilized β-Gal-mediated conversion of lactose in the HFMR.